Hakikat Perkembangan Ontologi Pendidikan Aqidah dalam Perspektif Filsafat Ilmu - Dita Aulia Rahmah; Izzatin Nisa'; Masyhuri Machfudz (IKIP Budi Utomo Malang, 2021)
The islamic creed is based on faith and monotheism in Allah SWT. Noble morals come from faith, and if someone's faith is good, then noble morals will be awakened so that one's religious behaviour will be good. Education of aqidah is closely related to student behaviour levels, for example, the subject matter of speaking ethics, so in this material, students are taught how to speak to teachers, parents, and fellow friends. Thus, with regard to student discipline, students are accustomed to asking permission from the teacher when leaving or entering the classroom during the teaching and learning process. This study used a qualitative design with a phenomenological approach. The data source is taken from the documentation. In this study, the teacher applies the curriculum with programmed material and carries out evaluations to measure how much students understand the material taught.